PENCAK JAIPONGAN BY CHOREOGRAPHER GUGUM GUMBIRA - Mulyadi , Tubagus (Acintya, 2024)
Jaipongan has been recognized as a creation dance in West Java. The dance genre derived from Ketuk Tilu and Pencak Silat has made Jaipongan an icon of Sundanese Dance. The purpose of this research is to explore how the development of pencak silat movements in the Jaipongan Dance created by Gugum Gumbira the creator of Jaipongan. Qualitative research methods were applied to collect data through a literature review of references relevant to the topic of study and documentation on videos of several Jaipongan works. The motion characteristics of Jaipongan were analyzed through Keser Bojong, Rendeng Bojong, Kawung Anten, and Pencug Bojong. The creation of Jaipongan was an outgrowth of Gugum Gumbira's experience as a dancer of Ketuk Tilu, Bajidoran, and Pencak Silat. Gugum's understanding and mastery of these three West Javanese folk dance genres led him to choreograph Jaipongan as a phenomenal new creation dance genre in West Java. The footwork technique is the foundation of the dance, to avoid the danger of slipping while dancing with the agile and attractive character of Jaipongan Dance. Therefore, mastery of pencak movement is important to be able to dance Jaipongan aesthetically.